Pelatihan Pengembangan Media Smart Video Adaptive Berbasis H5P dalam Mendukung Pembelajaran Matematika Berdiferensiasi : (Training on Developing Smart Adaptive Video Media Using H5P to Support Differentiated Mathematics Instruction) - Sofnidar, Sofnidar; Anwar, Khairul; Kamid, Kamid; Iriani, Dewi; Alrizal , Alrizal (Laboratorium Pembelajaran FKIP Universitas Jambi, 2025)
This study focuses on training for the development of adaptive learning media using H5P to support differentiated mathematics instruction at the Junior High School Mathematics Teachers' Forum (MGMP) in Jambi City. In line with the implementation of the Merdeka Belajar curriculum, teachers are required to provide materials that are responsive to the individual learning needs of students. This training aims to enhance teachers' skills in creating interactive learning media that can be tailored to diverse student abilities. The methods employed in this training include needs assessment, intensive workshops, and classroom media implementation. The results of this training show a significant improvement in teachers' competence in using H5P to produce interactive and adaptive media. This training is expected to support more personalized mathematics learning and increase student engagement in the learning process. Abstrak. Studi ini berfokus pada pelatihan pengembangan media pembelajaran adaptif menggunakan H5P untuk mendukung pembelajaran matematika yang terdiferensiasi di MGMP Matematika SMP Kota Jambi. Seiring dengan penerapan kurikulum Merdeka Belajar, guru-guru dituntut untuk menyediakan materi yang responsif terhadap kebutuhan belajar individu siswa. Pelatihan ini bertujuan untuk meningkatkan keterampilan guru dalam menciptakan media pembelajaran interaktif yang dapat disesuaikan dengan kemampuan siswa yang beragam. Metode yang digunakan dalam pelatihan ini meliputi survei kebutuhan, workshop intensif, dan implementasi media di kelas. Hasil dari pelatihan ini menunjukkan peningkatan signifikan dalam kompetensi guru dalam menggunakan H5P untuk menghasilkan media yang interaktif dan adaptif. Diharapkan, pelatihan ini dapat mendukung pembelajaran matematika yang lebih personal dan meningkatkan keterlibatan siswa dalam proses belajar.